Optimasi Susunan Bahan Makanan Bagi Anak Penderita Attention Deficit Hyperactivity Disorder (ADHD) Menggunakan Algoritme Genetika - Muhammad Taufan; Imam Cholissodin; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Proper nutrition can reduce symptoms of Attention Deficit Hyperactivity Disorder (ADHD). However, children are easily bored when given the same food constantly. In addition, food prices are also considered by parents. In this study sought the optimal solution of the problem of food ingredient preparation using genetic algorithm. To solve this problem, we use an integer permutation representation with chromosome length of 12 genes per day. These genes are a representation of a diet consisting of carbohydrates, proteins, and fats. The crossover method used is one-cut point, while for mutation method using exchange mutation. For the selection stage, elitism selection method is used. From the results of tests that have been done, we obtain optimal parameters that is 50 generations with an average fitness value obtained 13,928. The final result obtained is the composition of the food ingredient in accordance with the number of days desired.